Cocaine use disorder is associated with widespread surface-based alterations of the basal ganglia. (February 2023) - Xu, Hui; Xu, Cheng; Guo, Chenguang
Abstract: Cocaine use is a major public health problem with significant negative consequences at the individual and societal levels. Cocaine use disorder (CUD) is closely associated with brain structure alterations, which are mainly analyzed using voxel-based morphometric and traditional volumetric methods with certain limitations. This study conducted vertex-wise shape analysis to examine the effects of cocaine use on surface-based alterations of the basal ganglia in CUD. A total of 68 CUD individuals and 52 matched healthy controls (HCs) were enrolled in the study and underwent MRI scans and clinical measures. There were no significant differences in the volume of brain tissues and subcortical structures between groups. Related to HCs, CUD individuals showed regional surface atrophy of the left medial anterior thalamus, right medial posterior thalamus, and right dorsal anterior caudate, which were found to exhibit more significant surface atrophy in CUD individuals with onset age of cocaine use below 18. Furthermore, surface-based alteration of the right dorsal anterior caudate was significantly associated with years of cocaine use and the onset age of cocaine use in CUD individuals. Furthermore, both CUD individuals with onset age of cocaine use below 18 and CUD individuals with onset age of cocaine use above 18 showed similar significant relationship patterns between regional surface alteration of right dorsal anterior caudate and the onset age of cocaine use. These findings shed light on the effect of cocaine use on basal ganglia, help us understand the neural basis of cocaine dependence, and further provide effective interventions for CUD.